The Legal Impact of Prejudicial Decisions that State Invalidity of Suspects Determination - Iqbal Parikesit; Umar Ma'ruf; Peni Rinda Listyawati (Universitas Islam Sultan Agung, 2022)
In judicial practice, there have been several pre-trial decisions declaring the stipulation of a suspect invalid. The impression that arises from the suspect is as if the determination of the suspect is declared invalid, then the case is stopped and not continued. Therefore, this study aims to find out the legal impacts of prejudicial decisions which state the invalidity of the determination of suspects in the current and future laws. This study used a normative legal approach by reviewing and researching primary legal materials consisting of the Legislation on the Criminal Procedure Code (KUHAP) and Judge's Decisions. Then proceed with secondary legal materials in the form of books and journal articles related to pre-trial decisions declaring the determination of the suspect invalid. The analytical technique used in this research is a descriptive qualitative method. The results of the research on the legal impacts of the prejudicial decision stating the invalidity of the determination of the suspect, including (1) The investigation can still be continued even though there has been a pre-trial decision stating the stipulation of the suspect is invalid, (2) If before the determination of the suspect is declared invalid by the pre-trial judge, the suspect has an investigation is carried out by the investigator, the Minutes of Examination or “Minutes of Examination” of the suspect becomes invalid, (3) Legal actions based on the results of the suspect's examination are considered invalid, (4) Legal actions that are not based on the results of the suspect's examination are still valid and (5) If the investigation is continued and the investigator is able to find the suspect, the investigator may re-determine the suspect. Then against the determination of the suspect, the suspect can still apply for a pre-trial again, and so on.